Transplantation of fetal ventral mesencephalic progenitor cells overexpressing high molecular weight fibroblast growth factor 2 isoforms in 6-hydroxydopamine lesioned rats. (12th February 2015) - Rumpel, R.; Hohmann, M.; Klein, A.; Wesemann, M.; Baumgärtner, W.; Ratzka, A.; Grothe, C.
Highlights: FGF-2-HMW transfection increased DA cell number of short-term cultures in vitro . Histological analysis of DA grafts showed no differences after 13 weeks in vivo . Large graft groups improved similarly in behavioral tests (amphe, apo, cylinder). Abstract: Fibroblast growth factor-2 (FGF-2) is a potent neurotrophic factor promoting survival of dopaminergic (DA) neurons in vitro and in vivo . FGF-2 is expressed in different isoforms representing distinct translation products from a single mRNA. For this study, we focused on the high molecular weight (HMW) isoform, which, after non-viral plasmid-based overexpression in embryonic day 12 (E12) rat ventral mesencephalon (VM)-derived cells, revealed increased numbers of tyrosine hydroxylase-positive (TH + ) cells in a 'colayer' cell culture model. To determine the therapeutic potential of VM cells producing FGF-2-HMW as their 'own' neurotrophic factor, we transplanted cell suspensions obtained from such in vitro modified and differentiated cell cultures into the 6-hydroxydopamine (6-OHDA) hemiparkinsonian rat model. Animals, having received either non-transfected cells, empty-control transfected, or FGF-2-HMW-plasmid transfected cells, were analyzed in two different transplantation paradigms each using 172, 000 or 520, 000 cells, respectively. The behavioral performances in the amphetamine- and apomorphine-induced rotational test as well as in the cylinder test were evaluated for up to thirteen weeks post transplantation (postTX). Finally, the integration of the grafted cells into the host striatum was analyzed by immunohistochemical measurements. Those analyses revealed improvements of behavioral deficits in all five groups receiving DA neuron grafts, except for amphetamine-induced rotation of the FGF-2-HMW small graft group. Altogether, genetic modification with the FGF-2-HMW-plasmid did not further improve functional recovery compared to the control groups and had no influence on either the number of surviving DA neurons or on the density of outgrowing TH + fibers.